Peranan Ta’limul Muta’allim dalam Pembelajaran Modern - Syahid, Nur (SCHOLASTICA: Jurnal Pendidikan dan Kebudayaan, 2022)
The book ta'limul muta’allim is a book that discusses learning methods, learning objectives, learning principles, learning strategies and so on which as a whole aims to guide a person on morals and morality. Akhlakul karimah are all good or praiseworthy deeds that are embedded in the human soul which will then become a good habit. The aim of morals is for humans to be virtuous, behave, behave well towards God and towards fellow creatures, so that he will become higher and more perfect than other creatures and get the blessing of Allah SWT, to finally get the happiness of the world and the hereafter. The book of taklim which is actually one of the books that discusses how a person's morality begins to enter the world of education so that he can get useful knowledge. Then mastering the material of the book Ta'limul Muta'allim will give effect to the formation of students' morality since the learning process. Mastery of the material ta'limul muta'allim will provide an understanding of what knowledge must be known, what is the purpose of seeking knowledge in the view of Islam and how they respect teachers and others.